Pertanggungjawaban Perdata Affiliator E-Commerce atas Pelanggaran Hak Ekonomi Pencipta Video TikTok (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of digital platforms such as TikTok has encouraged the emergence of affiliate-based marketing practices in e-commerce activities. Affiliate marketing is a digital marketing system that promotes another person's product or service through a special affiliate link and earns a commission if a purchase or transaction is made through that affiliate link. Product promotion content has become one of the most effective marketing methods in the digital world. However, in practice, there are cases where affiliates reuse video content belonging to creators for promotional purposes and to earn sales commissions without permission. This study aims to analyze the provisions of digital video copyright protection under Law Number 28 of 2014 concerning Copyright and to examine forms of copyright infringement in the use of TikTok videos by affiliates. The method used is a normative study, employing a legal approach, a conceptual approach, and factual analysis. Primary and secondary legal materials were used in this study, which was analyzed descriptively and qualitatively. The results of the study show that TikTok videos fall under the category of cinematographic works that are protected as stipulated in Article 40 paragraph (1) letter m of the Copyright Law. Copyright protection arises automatically based on the declarative principle since the creation is realized in a tangible form, covering moral and economic rights. The use of TikTok videos by affiliates for promotional purposes and to earn sales commissions constitutes commercial use which, if done without the creator's permission, violates the creator's economic rights as stipulated in Article 9 paragraph (3) and potentially violates moral rights under Article 5 of the Copyright Law.